Lexical and Phrasal Semantic Extension of Japanese Color Words Based on Metonymic Motivation - Maarif, Samsul (Universitas Muhammadiyah Yogyakarta, 2020)
Research on semantic extension is concerned with words that develop a new, separate, but related meaning from their core sense. By using corpus data, this paper seeks to identify the extended meaning of Japanese color words on a phrasal level and reveal the cognitive processes behind their extended meaning. The corpus data show that metonymy is one of the most common routes for conveying the extended meaning of Japanese color words. This paper, therefore, proposes a model of semantic extension of such color words based on metonymy.